Arabic language learning anxiety in Chinese social media: a study of discursive habitus and language symbolism - Lian, Chaoqun (Onomázein, 2021)
Arabic language learning anxiety (AA) is common among Arabic learners in China. Its causes lie beyond the language and its structural features per se but elsewhere in the sociopolitical world. Analyzing discussions on Arabic learning on the Chinese social media site Zhihu and identifying the discursive habitus, i.e., statements recurrently made and strategies recurrently used in these discussions, this paper shows that AA is both a symptom of and a reaction to the entanglement of Arabic via language symbolism in three longue dureé sociopolitical circumstances: the building of the modern Chinese nation, the redefining of the Muslim constituents of the Chinese national identity, and power negotiation in the modern world-system of knowledge.